Electrospray-Assisted Ultraviolet Aerodynamic Particle Sizer Spectrometer for Real-time Characterization of Bacterial Particles - Jung, Jae Hee; Lee, Jung Eun; Hwang, Gi Byoung; Lee, Byung Uk; Lee, Seung Bok; Jurng, Jong Soo; Bae, Gwi Nam (AMER CHEMICAL SOC, 2010)
The ultraviolet aerodynamic particle sizer (UVAPS) spectrometer is a novel, commercially available aerosol counter for real-time, continuous monitoring of viable bioaerosols based on the fluorescence induced from living microorganisms. For aerosolization of liquid-based microorganisms, general aerosolization methods such as atomization or nebulization may not be adequate for an accurate and quantitative characterization of the microorganisms because of the formation of agglomerated particles. In such cases, biological electrospray techniques have an advantage because they generate nonagglomerated particles, attributable to the repulsive electrical forces among particles with unipolar charges. Biological electrosprays are quickly gaining potential for the detection and control of living organisms in applications ranging from mass spectrometry to developmental microbiology. In this study, we investigated the size distribution, total concentration, and fluorescence percentage of bacterial particles in a real-time manner by electrospray-assisted UVAPS. A suspension containing Escherichia coli as a test microorganism was sprayed in a steady cone-jet mode using a specially designed electrospray system with a point-to; orifice-plate configuration based on charge-reduced electrospray size spectrometry. With the electrospray process, 98% of the total E. coli particle number concentration had a size of <1 mu m and the geometric mean diameter was 0.779 mu m, as compared with the respective values of 78% and 0.907 mu m after nebulization. The fractions of fluorescence responsive particles and of particles that contained viable organisms in culture were 12% and 7%, respectively, from the electrospray process and 34% and 24% from nebulization. These results demonstrate that (1) the presence of agglomerated particles can lead to markedly overestimated fluorescence and culturability percentages compared with the values obtained from nonagglomerated particles, and (2) electrospray-assisted UVAPS can provide more accurate and quantitative real-time characterization of liquid-based microorganisms, owing to the generation of nonagglomerated particles.
Keywords: FLUORESCENCE-SPECTRUM ANALYZER; MONODISPERSE WATER DROPLETS; MASS-SPECTROMETRY; CHARGE REDUCTION; ELECTROPHORETIC MOBILITY; AIRBORNE MICROORGANISMS; ESCHERICHIA-COLI; BIOAEROSOLS; GENERATION; UVAPS